A Survey of the Bachelor of Physical Education (BPEd) Program's Awareness, Acceptability and Alignment with the University's Vision, Mission, Goals and Objectives - Andy B. Ramos (RIRAI Publisher, 2021)
Every organization's vision, mission, goals, and objectives dictate its existence and direction (VMGO). Each state, university, and institution has its own VMGO, which will direct the system's strategic plans, initiatives, and activities, as well as its operations. The study determined the awareness level, acceptance, and consistency of the university's vision and mission, goals of the college, and the BPEd program objectives among students, faculty, and stakeholders. The descriptive research method was used. Students enrolled in the Bachelor of Physical Education program, faculty, and other stakeholders were the respondents of the study, with a total of 80 out of 218 respondents. A survey questionnaire was used in gathering the data. The analyzed and summarized data were then organized into a series of tables in accordance with the study's objectives. Frequency counts, percentages, and averages were utilized as descriptive statistics. The study over all revealed that stakeholders are fully aware and accept VGMO’s key statements. It is also revealed from their response that the statements of the VGMO and the program activities are very much congruent. Hence, VMGO’s statements’ dissemination campaign and strategies are effective. This indicates further sustainability for growth and development.